2010
DOI: 10.1007/s12032-010-9534-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PG-SGA, SGA and body-composition measurement in detecting malnutrition among newly diagnosed lung cancer patients in stage IIIB/IV and benign conditions

Abstract: Assessment tools and body-composition measurements are useful in diagnosing malnutrition. Which one is better for lung disease patients is unclear. The objectives of the present study are: to assess relationships between different methods of nutritional measurements in lung diseases patients; to determine which one is better in diagnosing malnutrition for lung disease patients; and to determine whether lung cancer patients can be differentiated from benign lung disease patients using different measurements. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 27 publications
(27 reference statements)
1
33
0
1
Order By: Relevance
“…Subjective assessment of nutritional status is commonly used to supplement objective measures, and PG-SGA has been shown to be effective in assessing nutritional status in cancer patients [ 49 , 50 ]. At the initiation of the study, all patients were rated as moderately to severely malnourished.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective assessment of nutritional status is commonly used to supplement objective measures, and PG-SGA has been shown to be effective in assessing nutritional status in cancer patients [ 49 , 50 ]. At the initiation of the study, all patients were rated as moderately to severely malnourished.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that the influence of BMI on survival time differs from each other, [ 5 9 ] and other indexes such as weight and albumin are also unstable. [ 10 ] PG-SGA is highly recommended by nutritionists and can be easily applied in leukemia patients. Thus, we aimed to evaluate the nutritional status of adult patients with AL using PG-SGA and to investigate the influence of nutritional status on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 ] Various nutritional evaluation tools such as body mass index (BMI), weight loss, biochemical indexes, and body composition are applied in different studies, yielding inconsistent results. [ 5 10 ] This situation is a main factor limiting leukemia-related nutritional research.…”
Section: Introductionmentioning
confidence: 99%
“…Other trials have been limited to patients with a particular entity, for example patients with lung cancer. 35…”
Section: Original Reportmentioning
confidence: 99%